Preventing college student nonmedical prescription stimulant use: Development of vested interest theory-based persuasive messages - Donaldson, Candice D.; Siegel, Jason T.; Crano, William D. (Addictive behaviors, 2020)
[Display omitted] •Studied effects of messages to minimize the nonmedical use of prescribed stimulants (NUPS).•Effects of messages based on vested interest theory were evaluated experimentally.•Messages argued NUPS did not enhance cognitive functioning for non-ADD students.•VIT-based messages decreased vested interest beliefs and usage intentions.•There were no significant effects of a physical harm comparison message. Vested interest theory (VIT) predicts that perceived importance and hedonic relevance of an expected behavioral outcome affects attitude-behavior consistency. Applied to college students’ nonmedical use of prescription stimulants (NUPS), the theory posits that persuasive information that weakens vested perceptions regarding assumed advantages of stimulant misuse will reduce usage intentions. The current study developed and experimentally assessed persuasive messages that targeted perceptions of vested interest (VI), and examined if message effectiveness varied as a function of users’ risk status. Appeals that focused on the physical harms of misuse served as the comparison condition. College student participants (N = 282) were randomly assigned to one of four message conditions. To examine group differences, data were analyzed in a 2 (VIT-based message: yes, no) × 2 (Physical harms emphasized: yes, no) × 3 (User status: resolute, vulnerable, user) between-subjects factorial design. Analyses showed that messages focused on lowering VI by convincing students that NUPS did not enhance cognitive functioning of non-ADD/ADHD students reduced perceived vested interest (p < .001) and attitude favoribility p = .005. In vulnerable nonusers, these messages also decreased NUPS intentions p = .006. The effect of exposure to the physical harm communication was not significant. Findings support the potential of VIT-guided messages in NUPS prevention, and the lack of effect of messages focused on physical consequences of misuse.